Screen time and adolescent well-being: a comparative study of Russia and Cuba - Dmitry Kornienko; Natalia A. Rudnova; Aleksander Veraksa; Jorge Enrique Torralbas Oslé; Apollinaria Chursina; Emely Corcho Rosales (Frontiers in Public Health)
IntroductionThe increasing prevalence of devices with unrestricted internet connectivity among the younger population gives rise to a novel environment for social interaction and cognitive processing. Most research have concentrated on adolescents in the Western countries, addressing the influence of screen time on their social and cognitive growth. The objective of the study was to examine the association between the amount of time spent on screens and the presence of health and well-being problems among adolescents from Russia and Cuba. Considering the prevailing worldwide pattern of excessive internet usage and social media consumption, we expect to observe rare and minor variations in screen time and its effects on health and well-being.MethodsThe sample consists of 524 adolescents between the ages of 13 and 18 (M = 15.6; SD = 1.28), with 58.7% female. The study included 224 people residing in Cuba and 300 participants residing in Russia. The online survey comprises inquiries regarding internet and gadget usage duration, addiction to social media, positive and negative affects, and items for evaluating screen time induced problems, and preferred content.ResultsThere are significant differences in the amount of time spent on screens, addiction to social media, overall well-being, and health issues among adolescents from Russia and Cuba. Adolescents in Russia exhibited elevated levels of internet usage and engagement on social media platforms; however, they experienced an increase in cognitive and family-related issues. Cuban adolescents, in turn, experience more negative affect and problems with basic needs due to excessive Internet use.ConclusionGenerally, irrespective of their country of residence, teenagers who spend more time on screens tend to encounter a higher prevalence of health and well-being problems. The environment of Russian adolescents is significantly more like European countries in terms of Internet use, which has led to an increase in screen time and various health and psychological issues. In contrast, Cuban teenagers experience increased issues with family relationships because of screen time. The findings are consistent with prior research that have shown a correlation between increased internet usage and adverse outcomes.